The Use of Verb Tenses in Subordinate Content Clauses in Czech - Koutová, Marta (Bohemistyka, 2022)
Research on the use of verb tenses in Czech subordinate clauses is based on the notions of absolute and relative tense and on the distinction between content and adjunct clauses. It is generally agreed that absolute tenses are used in adjunct clauses, whereas relative tenses are typically used in content clauses. Based on an analysis from the Czech National Corpus, I will demonstrate that, in addition to the assumed use of tenses and in contrast to their usage in English, there are also variations in their use: in content clauses, even tenses selected from the speaker’s perspective are used in certain cases, and in certain adjunct clauses relative tenses may also be used.